Exposure of Human CD4 T Cells to IL-12 Results in Enhanced TCR-Induced Cytokine Production, Altered TCR Signaling, and Increased Oxidative Metabolism - Vacaflores, Aldo (PLoS One, 2016)
Human CD4 T cells are constantly exposed to IL-12 during infections and certain autoimmune disorders. The current paradigm is that IL-12 promotes the differentiation of naïve CD4 T cells into Th1 cells, but recent studies suggest IL-12 may play a more complex role in T cell biology. We examined if exposure to IL-12 alters human CD4 T cell responses to subsequent TCR stimulation. We found that IL-12 pretreatment increased TCR-induced IFN-γ, TNF-α, IL-13, IL-4 and IL-10 production. This suggests that prior exposure to IL-12 potentiates the TCR-induced release of a range of cytokines. We observed that IL-12 mediated its effects through both transcriptional and post-transcriptional mechanisms. IL-12 pretreatment increased the phosphorylation of AKT, p38 and LCK following TCR stimulation without altering other TCR signaling molecules, potentially mediating the increase in transcription of cytokines. In addition, the IL-12-mediated enhancement of cytokines that are not transcriptionally regulated was partially driven by increased oxidative metabolism. Our data uncover a novel function of IL-12 in human CD4 T cells; specifically, it enhances the release of a range of cytokines potentially by altering TCR signaling pathways and by enhancing oxidative metabolism.